Gold-based nanoparticles realize photothermal and photodynamic synergistic treatment of liver cancer and improve the anaerobic tumor microenvironment under near-infrared light - Li, Bei; Fu, Yi; Xie, Maodi; Feng, Lei; Niu, Xiaoya; Que, Lin; You, Zhen (Frontiers in Bioengineering and Biotechnology, 2022)
In order to solve the different pain caused by traditional cancer treatment methods such as surgical treatment, the nano drug delivery system provides new ideas for cancer treatment. In this paper, a novel anti-tumor therapy nanoparticle P(AAm-co-AN)-AuNRs@CeO2-Ce6(PA/Ce6) is prepared, which provides a novel idea for liver cancer treatment. The CeO2-coated gold nanorods were grafted onto the surface of the temperature-sensitive polymer P(AAm-co-AN)-CTPD. The photosensitizer Ce6 is loaded on the surface of the nanoparticles and the polymer layer. CeO2 can effectively alleviate the tumor anaerobic microenvironment, and under 808 nm near-infrared excitation, the gold nanorods achieve photothermal conversion to induce local heating, which leads to the phase transition of the polymer layer and realizes a controllable release mechanism. In addition, 660 nm near-infrared light can effectively induce Ce6 to produce singlet oxygen, thereby effectively killing cancer cells. Under the 808 nm laser irradiation within 600 s, the PA/Ce6 solution can heat up to about 60℃, which was enough to ablate both cancer cells and tumor tissues. When the temperature was 50℃, the cumulative release rate of Ce6 was 95.31%. Under the 808 nm laser irradiation, oxygen production capacity of PA/Ce6 was higher and can effectively reduce the content of hydrogen peroxide in cancer cells. Compared to free Ce6, the reactive oxygen species (ROS)-mediated fluorescence of PA/Ce6 nanoparticles was greater. The cell viability and migration of HepG2 cells were decreased after the 660 nm and 880 nm lasers were irradiated at the same time. The cancer cells were further inhibited, showing a good in vitro anti-tumor effect. PA-DOX showed the best tumor growth inhibitory effect under NIR laser irradiation and had no acute toxicity in vivo. Due to the existence of AuNRs, nanoparticles had high-efficiency photothermal conversion ability to achieve PTT therapy. And Ce6 can generate singlet oxygen under the excitation of 660 nm laser to realize PDT therapy. The experimental results also shown that PA/Ce6 can effectively decompose hydrogen peroxide under laser irradiation, aiming to effectively alleviate the anaerobic microenvironment of tumors. These indicate that PA/Ce6 plays a promising role for HCC treatment.